2013
DOI: 10.1371/journal.pone.0074521
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase Gene Polymorphism and Risk of Type 2 Diabetes Mellitus

Abstract: ObjectiveThis review aimed to comprehensively assess the literature examining a possible link between the rs1801133 polymorphism (677C→T) in the gene encoding the methylenetetrahydrofolate reductase (MTHFR) gene and risk of type 2 diabetes mellitus (DM).Research Design and MethodsSeveral research databases were systematically searched for studies examining the genotype at the rs1801133 polymorphism in healthy control individuals and individuals with type 2 DM. Genotype frequency data were examined across all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 56 publications
0
28
0
2
Order By: Relevance
“…However, the results were not consistent [13][19]. A systematic review on Arab ethnicity found that MTHFR C677T polymorphism was significantly associated with T2DM [14], but another systematic review found that there was no association between MTHFR C677T polymorphism and T2DM around the world, similar results were repeated for ethnic group (Asian, Caucasian, African) [13].…”
Section: Introductionmentioning
confidence: 98%
“…However, the results were not consistent [13][19]. A systematic review on Arab ethnicity found that MTHFR C677T polymorphism was significantly associated with T2DM [14], but another systematic review found that there was no association between MTHFR C677T polymorphism and T2DM around the world, similar results were repeated for ethnic group (Asian, Caucasian, African) [13].…”
Section: Introductionmentioning
confidence: 98%
“…Due to the divergent results among single‐country studies, several systematic meta‐analyses have been undertaken to determine conclusively whether MTHFR C677T is associated with the risk of T2DM. In 2013, Chinese academics Zhong, Rodriguez, Yang, and Li () conducted a meta‐analysis regarding MTHFR C677T and T2DM. Their meta‐analysis included 4,855 T2DM patients and 5,242 controls.…”
Section: Discussionmentioning
confidence: 99%
“…A significant association of Ala allele with retinopathy in Caucasians was observed; however, o significant results were observed in association with T2DM and the other related complications. No association of the C677T polymorphism of MTHFR gene was found in Africans, Asians, and Caucasians (48). MTHFR is a gene that is involved in DNA methylation and synthesis along with the regulation of folate activity.…”
Section: Genetics Of Type 2 Diabetes In South Asian Populationmentioning
confidence: 99%